Calorie Intake and Factors Associated with Food Consumption - Lwin, Mar Mar; Khin, Cho Aung; Cliffton, Akoi; Khin, Than Yee (Malaysian Society of Applied Biology, 2018)
Medical students experience time constraints and stress in studying, thus, they tend to have an imbalanced diet. This study assessed the calorie intake and factors associated with food consumption among medical students in the Faculty of Medicine and Health Sciences of Universiti Malaysia Sarawak. The self-administered questionnaires regarding the knowledge and attitude about food consumption, factors affecting food intake and a 24-hour dietary recall was completed by 101 students. They had overall good knowledge on food consumption, calorie content, hygienic food preparation and balanced diet, 52.5% had normal BMI, 80.2% considered to reduce fast food consumption, and 76.2% consumed food for the tastiness. There was a significant correlation between respondents’ knowledge and total calorie intake (p<0.05). The main factors affecting food consumption are types of food chosen, amount of food taken and frequency of meals consumed. The total calorie intake differs between male and female. Majority of the students had one to two servings of fruit per day. The knowledge plays an important role in total calorie intake. The results suggest that the subjects were more concerned about the taste of the food rather than the cost and nutritional value.